Transcoronary infusion of bone marrow derived multipotent stem cells to preserve left ventricular geometry and function after myocardial infarction - Sarana Boonbaichaiyapruck (2018)
Objectives: Myocardial damage aftermyocardial infarction(MI)was deemed irreversible after late reperfusion. Administrationofmultipotent stem cells (MSC) into such infarctmay regenerate themyocardiumand capillary network. The objectives were to study the feasibility and safety of MSC infusion and its effect on infarct size and left ventricular (LV) function. Methods: We conducted a pilot study in patients who survived ST-elevation MI with late reperfusion therapy and remained hemodynamically stable. Bone marrow derived MSC was infused into a patent infarct-related coronaryartery during brief lowpressure (2 atm) balloon inflation. A 3-T gadolinium-based MRI was performed at baseline and 8 weeks later to evaluate infarct area and LV function. Results: We enrolled 10 patients, age 63.8±2.8 years 5.2±4.12 × 106MSC were infused via coronary artery 24.8±16 days after infarction. The procedures were successful in all patients without any in-hospital event. Infarct size by MRI decreased by 5.84% (P = .018) over 8 weeks. Mean baseline left ventricular ejection fraction (LVEF) was 44.1% ± 9% and was 46.3%±9% at 8 weeks (P = .34). A trend of smaller LV end-systolic volumewith 65.02±18.2 ml vs63.04±21.89 ml (P = .09)with no change of LV end-diastolic volume observed. Conclusion: MSC infusion into coronary circulation was feasible and safe after myocardial infarction. Infarct size was reduced with preservation of LV geometry. © 2010Wiley Periodicals, Inc.